2013
DOI: 10.1155/2013/265105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pediatric and Adult Tonsillectomies Performed by Thermal Welding System

Abstract: Objective. To compare pediatric and adult age groups in terms of postoperative bleeding and pain following tonsillectomy performed by thermal welding system (TWS). Method. The study consisted of 213 patients, of whom 178 were children and 35 were adults. The mean age of the pediatric patients (81 girls and 97 females) was 6.7 ± 2.4 years (range 3–13 years) and the mean age of the adults (20 males and 15 females) was 21.8 ± 7.07 years (range 15–41 years). All of the patients were evaluated in terms of postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Older children and those with recurrent tonsillitis may experience greater pain than young children with obstruction. [24][25][26][27][28] In this study, 22 children were older than 6 years (14 and 8 in the LTD and ES groups, respectively) and 13 children had recurrent tonsillitis (6 and 7 in the LTD and ES groups, respectively). Thus, it is unlikely that older age or diagnosis explains the greater pain medication use in the ES group.…”
Section: Discussionmentioning
confidence: 75%
“…Older children and those with recurrent tonsillitis may experience greater pain than young children with obstruction. [24][25][26][27][28] In this study, 22 children were older than 6 years (14 and 8 in the LTD and ES groups, respectively) and 13 children had recurrent tonsillitis (6 and 7 in the LTD and ES groups, respectively). Thus, it is unlikely that older age or diagnosis explains the greater pain medication use in the ES group.…”
Section: Discussionmentioning
confidence: 75%
“…Although postoperative bleeding was seen in the group treated with cold technique, difference was not statistically significant. In the study of Ersozlu et al (2013) based on 213 adults and pediatric patients, postoperative bleeding was observed in both age groups but especially in adult age group.…”
Section: Discussionmentioning
confidence: 99%
“…Older age at surgery has previously been described as a risk factor for short-term complications especially when focusing on postoperative hemorrhage and pain ( 16 18 ). The reason for this is not fully understood, and older age also seems to be an individual risk factor in studies using multivariable regression models ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%